1991
DOI: 10.1111/j.1528-1157.1991.tb04666.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Versus Medical Treatment for Epilepsy. I. Outcome Related to Survival, Seizures, and Neurologic Deficit

Abstract: We conducted a retrospective parallel longitudinal cohort study comparing surgical and medical treatment for epilepsy. The surgical group contained 201 patients treated with resective surgery for epilepsy in Norway since the first operation in 1949 until January 1988. The 185 control group patients treated medically only were closely matched for year of treatment, age at treatment, sex, seizure type, and neurologic deficit before treatment. There was no significant difference in survival between the two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 19 publications
4
34
0
4
Order By: Relevance
“…One study considered students and persons in a sheltered workshop as being employed (10). Others relied on measures undefined (14,15) or subjective (11,(16)(17)(18) measures (e.g., work "ability," "capacity," "performance," or "career outcome.") Heretofore, only five studies (10,14,16,17,19) statistically analyzed their data, and only one (19) demonstrated significant improvement in unemployment rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study considered students and persons in a sheltered workshop as being employed (10). Others relied on measures undefined (14,15) or subjective (11,(16)(17)(18) measures (e.g., work "ability," "capacity," "performance," or "career outcome.") Heretofore, only five studies (10,14,16,17,19) statistically analyzed their data, and only one (19) demonstrated significant improvement in unemployment rates.…”
Section: Discussionmentioning
confidence: 99%
“…Others relied on measures undefined (14,15) or subjective (11,(16)(17)(18) measures (e.g., work "ability," "capacity," "performance," or "career outcome.") Heretofore, only five studies (10,14,16,17,19) statistically analyzed their data, and only one (19) demonstrated significant improvement in unemployment rates. Some studies (14,17,19) examined a limited number of factors as predictors of work outcome, but none performed multivariable analysis to identify factors that are independently predictive.…”
Section: Discussionmentioning
confidence: 99%
“…There have been no randomized trials of surgery for epilepsy, generally considered the "gold standard" study design for assessing this technology-intensive, invasive procedure (1). Previous reports of epilepsy surgery outcome are limited to longitudinal case series of surgical patients, without comparison with any reference group until the work of Guldvog et al (2,3). In that study, subjects were not identified prospectively, and researchers were unable to adjust for baseline differences between surgery and nonsurgery groups using statistical methods.…”
mentioning
confidence: 99%
“…Es existieren jedoch keine ausreichenden Daten, auf deren Grundlage Langzeitauswirkungen des Absetzens einer antikonvulsiven Medikation nach epilepsiechirurgischen Eingriffen beurteilt werden könnten. Mehrere Studien belegen, dass der Anteil von Patienten ohne Medikation nach epilepsiechirurgischen Eingriffen höher ist als in Kontrollgruppen [2,4,12,16,46]. Der Anteil epilepsiechirurgisch "heilbarer" Patienten ist jedoch derzeit unklar.…”
Section: Antikonvulsive Therapie Im Langzeitverlauf Nach Epilepsiechiunclassified